2021
DOI: 10.51253/pafmj.v71i3.4102
|View full text |Cite
|
Sign up to set email alerts
|

Diagnostic Accuracy of 99 MTC Labelled Ubiquicidin (29-41) Spect/Ct for Diagnosis of Osteomyelitis in Diabetic Foot

Abstract: Objective: To determine diagnostic accuracy of 99mTc labelled Ubiquicidin (29-41) SPECT/CT for detection of osteomyelitis in diabetic foot patients by taking bone biopsy as gold standard. Study Design: Cross-sectional validation study. Place and Duration of Study: Nuclear Medical Centre, Armed Forces Institute of Pathology, from Apr 2017 to Mar 2018. Methodology: Study assessed 122 patients of both genders, aged between 30-80 years (mean age=55.3 years), presenting with diabetic foot ulcers h… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
5
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(5 citation statements)
references
References 20 publications
0
5
0
Order By: Relevance
“…Data on the use of 18F‐FDG PET/CT as a discriminating tool between DFO and CNO still remain limited. Another study with low risk of bias showed 99% positive predictive value, and 57% negative predictive value with 94% diagnostic accuracy of 99mTc labelled Ubiquicidin SPECT/CT for the detection of osteomyelitis in patients with diabetes‐related foot ulcers 92 …”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…Data on the use of 18F‐FDG PET/CT as a discriminating tool between DFO and CNO still remain limited. Another study with low risk of bias showed 99% positive predictive value, and 57% negative predictive value with 94% diagnostic accuracy of 99mTc labelled Ubiquicidin SPECT/CT for the detection of osteomyelitis in patients with diabetes‐related foot ulcers 92 …”
Section: Resultsmentioning
confidence: 99%
“…Lauri 2017, 76 Ertugrul 2006, 77 Johnson 1996, 78 Nawaz 2010, 79 Newman 1992, 80 Shagos 2015, 81 Blume 1997, 82 Treglia 2013, 83 Rastogi 2016, 84 Abdel Razek 2017, 85 Aslangul 2013, 86 Poirier 2002, 87 Llewellyn 2020, 88 LaFontaine 2021, 89 Sax 2020, 90 Diez 2020, 91 Atif 2021 92 …”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…107 In patients with a contraindication to MRI, clinicians may choose other imaging techniques (e.g., FDG-PET/CT, HMPAO-labelled leucocyte scintigraphy or 99mTc labelled Ubiquicidin (UBI) SPECT/CT). [107][108][109][110][111][112] Compared to nuclear (e.g., leukocyte) imaging, PET, especially combined with CT scan, offers high spatial resolution, precise anatomic localization, possibly higher sensitivity for chronic infection, easier performance, faster results, and low radiation exposure.…”
Section: Rationalementioning
confidence: 99%
“…A systematic review and meta‐analysis that compared the diagnostic accuracy of imaging tests (plain X‐rays, scintigraphy, MRI, SPECT and PET) for the diagnosis of DFO showed that 18 F‐fluorodeoxyglucose (FDG)–PET and 99 mTc‐ exametazime Hexa Methyl Propylene Amine Oxime labelled WBC scintigraphy offer the highest specificity (0.92 for both) 107 . In patients with a contraindication to MRI, clinicians may choose other imaging techniques (e.g., FDG‐PET/CT, HMPAO‐labelled leucocyte scintigraphy or 99mTc labelled Ubiquicidin (UBI) SPECT/CT) 107–112 …”
Section: Recommendationsmentioning
confidence: 99%